(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Mathematics is called mirror of our civilization. It shapes our culture as a pioneer that is why it is said, Shut out mathematics from our daily life and all civilizations come to a standstill. It is wise to base our cause for mathematics on the common sense ground of everyday experience rather than on far-reaching theoretical considerations. Moreover, to draw the inferences that mathematics is an instrument of education found to be in conformity with the need of the human mind.